ANALISIS FAKTOR PELAYANAN, SARANA PRASARANA, KEUNIKAN OBJEK, DAN KEAMANAN YANG MEMPENGARUHI KETERTARIKAN WISATAWAN PADA PANTAI BARON GUNUNGKIDUL - Mentari Herdianingsih; Sukardi Sukardi (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine whether: service factors affect tourist attraction, infrastructure facilities influence tourist attraction, object uniqueness factors affect tourist attraction and security factors affect tourist attraction. And know the magnitude of the influence of factors of service, infrastructure, uniqueness of objects, and safety simultaneously on the attraction of tourists to Baron Gunungkidul Beach. The population in this study is the visitor / tourist attraction of Baron Beach. Samples taken as many as 100 respondents using the Accidental Sampling technique (sampling choose who happened to be / found) and using the Purposive Side technique that is deliberate sampling (researchers determine their own samples taken because there are certain considerations). Based on the results of research that has been tested: service has a positive and significant effect on tourist attraction, Infrastructure has a positive and significant effect on tourist attraction, The uniqueness of the object has a positive and significant effect on tourist interest, Security has a positive and significant effect on tourist interest and simultaneous service variables, infrastructure, uniqueness of objects and security have a significant effect on the attraction of tourism in the Baron beach tourism object. While the magnitude of the influence of the four independent variables on the dependent variable is 54.7%, and the remaining 45.3% tourist interest is influenced by other variables.